2021
DOI: 10.31557/apjcp.2021.22.3.853
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Outcome and Prognosis Factors of FIGO 2018 Stage III Cervical Cancer Patients Treated with Definitive Concurrent Chemoradiation in Vietnam

Abstract: Objective: This study aimed to analyze the treatment outcome and toxicities, along with prognosis factors of patients with FIGO 2018 stage III cervical cancer treated with definitive concurrent chemoradiation. Methods: A total of 83 stage III cervical cancer patients with good performance status (ECOG PS 0, 1) were treated with three-dimensional conformal radiation therapy (3D-CRT) combined with chemotherapy (weekly cisplatin), followed by high-dose-rate (HDR) brachytherapy between January 2017 and March 2019 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…At 3 years, the local control rate was 89.5e94.4%. At 3 years, DFS was 63.4e81.8% and overall survival was 64.6e89.5% [53,54]. Most of the published literature mentioned are from Thailand and China.…”
Section: South-east Asia and Chinamentioning
confidence: 99%
“…At 3 years, the local control rate was 89.5e94.4%. At 3 years, DFS was 63.4e81.8% and overall survival was 64.6e89.5% [53,54]. Most of the published literature mentioned are from Thailand and China.…”
Section: South-east Asia and Chinamentioning
confidence: 99%
“…Back in 1981, Piver et al [ 24 ] published American results on this matter with technology for diagnosis and treatment suitable for that era. More recently, other countries have also published their results, including a Vietnamese [ 25 ], Turkish [ 26 ], Japanese [ 27 ] and Chinese [ 28 ] study, all of them with samples smaller than the one presented here. Specifically, regarding Liu et al (2019) [ 28 ], that reported the outcomes of a number of patients (59) similar to our study (65), the three-year overall survival of 52.8% was comparable with 50.6% finding in our cohort.…”
Section: Discussionmentioning
confidence: 96%